![( f o g)(2) = (1)/(17)](https://img.qammunity.org/2020/formulas/mathematics/high-school/a3i80mrd71dlv7zp4cvjdrd1lu938ijylp.png)
![(f + g)(2) = (35)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/kplzxxue88whg2l6da54c1js6cv5be5cw0.png)
Solution:
Given that:
![f(x) = (1)/(x)\\\\g(x) = 4x + 9](https://img.qammunity.org/2020/formulas/mathematics/high-school/j3xi92shubktzzurkbc15c1dw7qfg624p6.png)
To find: (fog)(2) and (f + g)(2)
By composite function,
( f o g)(x) = f (g(x))
Substitute g(x) = 4x + 9 in above formula,
( f o g)(x) = f(4x + 9)
To find (fog)(2) substitute x = 2 in above formula
( f o g)(2) = f(4(2) + 9)
( f o g)(2) = f(8 + 9) = f(17)
We know that
![f(x) = (1)/(x)](https://img.qammunity.org/2020/formulas/mathematics/college/ntcaamqo6dt0nb2ujlnku2ik1c880kffjx.png)
![( f o g)(2) = f(17) = (1)/(17)](https://img.qammunity.org/2020/formulas/mathematics/high-school/903v7rkq8uv1o4h32ptmxj81uhhltv9osx.png)
![( f o g)(2) = (1)/(17)](https://img.qammunity.org/2020/formulas/mathematics/high-school/a3i80mrd71dlv7zp4cvjdrd1lu938ijylp.png)
To find (f + g)(2)
We know that,
(f + g)(x) = f (x) + g(x)
Therefore,
(f + g)(2) = f(2) + g(2)
Substitute x = 2 in f(x) and g(x)
![(f + g)(2) = (1)/(2) + (4(2) + 9)\\\\(f + g)(2) = (1)/(2) + 17 = (1+34)/(2) = (35)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/5k07eapokijw6z7qt05gpkcm417m264u53.png)
![(f + g)(2) = (35)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/kplzxxue88whg2l6da54c1js6cv5be5cw0.png)